Chilling Consequences: Recruitment Failure of Four Native Fish Species in a Thermally Polluted, Regulated River - Laura E. Michie; James N. Hitchcock; Simon M. Mitrovic; Matthew Gordos; Gavin L. Butler (Fisheries Management and Ecology, 2026)
Cold water pollution (CWP), caused by the release of unseasonably cool water from the bottom of large reservoirs to downstream rivers, is an escalating global threat to riverine biodiversity that is exacerbated by future dam developments and climate change. This study examined the impact of CWP on native fish populations in the Severn River (NSW, Australia), downstream of a large reservoir. Long‐term data (2012–2024) revealed chronic CWP, with thermal regimes frequently below thresholds required for native fish spawning during the austral summer period. An aged population structure and chronic recruitment failure were evident in four native fish species. Additionally, native fish stocking efforts have resulted in limited success. We recommend both long‐term CWP mitigation and immediate adaptive management strategies, such as optimising stocking practices and opportunistic water management actions, as critical to sustaining native fish populations.

Assessment of nicotine and degradation products in cigarette butts leachates after detoxification by white rot fungi - María del Pilar Núñez; Elsa Gabriela López Loveira; Sofía Eugenia Domínguez; Laura Mariel Calfayan; Raúl Fabio Itria; Matías Butler (Journal of Hazardous Materials, 2025)

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

3D Morphometric Analysis Reveals Similar Ecomorphs for Early Kangaroos (Macropodidae) and Fanged Kangaroos (Balbaridae) from the Riversleigh World Heritage Area, Australia - Kaylene Butler; Kenny J. Travouillon; Alistair R. Evans; Laura Murphy; Gilbert J. Price; Michael Archer; Suzanne J. Hand; Vera Weisbecker (Journal of Mammalian Evolution, 2021)

Enhanced light interception and light use efficiency explain overyielding in young tree communities - Laura J. Williams; Ethan E. Butler; Jeannine Cavender‐Bares; Artur Stefanski; Karen E. Rice; Christian Messier; Alain Paquette; Peter B. Reich (Ecology Letters, 2021)
Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here we investigated whether light interception alone or in combination with light use efficiency (LUE) of dominant and subordinate species explained greater productivity of mixtures relative to monocultures (i.e. overyielding) in 108 young experimental tree communities. We found mixed‐species communities that intercepted more light than their corresponding monocultures had 84% probability of overyielding. Enhanced LUE, which arose via several pathways, also mattered: the probability of overyielding was 71% when, in a mixture, species with higher ‘inherent’ LUE (i.e. LUE in monoculture) intercepted more light than species with lower LUE; 94% when dominant species increased their LUE in mixture; and 79% when subordinate species increased their LUE. Our results suggest that greater light interception and greater LUE, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests.

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Life cycle assessment of adsorbents for fluoride removal from drinking water in East Africa - Teshome L. Yami; Junyi Du; Laura R. Brunson; Jim F. Chamberlain; David A. Sabatini; Elizabeth C. Butler (The International Journal of Life Cycle Assessment, 2015)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Circulating levels of adipokines and IGF-1 are associated with skeletal muscle strength of young and old healthy subjects - Laura Bucci; Stella Lukas Yani; Cristina Fabbri; Astrid Y. Bijlsma; Andrea B. Maier; Carel G. Meskers; Marco V. Narici; David A. Jones; Jamie S. McPhee; Enn Seppet; Helena Gapeyeva; Mati Pääsuke; et al. (Biogerontology, 2013)

Age-dependent alteration in muscle regeneration: the critical role of tissue niche - Laura Barberi; Bianca Maria Scicchitano; Manuela De Rossi; Anne Bigot; Stephanie Duguez; Aurore Wielgosik; Claire Stewart; Jamie McPhee; Maria Conte; Marco Narici; Claudio Franceschi; Vincent Mouly; et al. (Biogerontology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Delineation of Source Protection Zones Using Statistical Methods - Fritz Stauffer; Alberto Guadagnini; Adrian Butler; Harrie-Jan Hendricks Franssen; Neeltje Van De Wiel; Mahmoud Bakr; Monica Riva; Laura Guadagnini (Water Resources Management, 2005)

Phosphorylation of a high molecular weight (∼600 kDa) protein regulates catch in invertebrate smooth muscle - Marion J. Siegman; Susan U. Mooers; Chenqing Li; Srinivasa Narayan; Laura Trinkle-Mulcahy; Shugo Watabe; David J. Hartshorne; Thomas M. Butler (Journal of Muscle Research and Cell Motility, 1997)